Hippocampal proton MR spectroscopy as a novel approach in the assessment of radiation injury and the correlation to neurocognitive function impairment: initial experiences - Pospisil, Petr; Kazda, Tomas; Bulik, Martin; Dobiaskova, Marie; Burkon, Petr; Hynkova, Ludmila; Slampa, Pavel; Jancalek, Radim (Radiation oncology (London, England), 2015)
BACKGROUND: The hippocampus is considered as the main radiosensitive brain structure responsible for postradiotherapy cognitive decline. We prospectively assessed correlation of memory change to hippocampal N-acetylaspartate (h-tNAA) concentration, a neuronal density and viability marker, by (1)H-MR spectroscopy focused on the hippocampus. METHODS: Patients with brain metastases underwent whole brain radiotherapy (WBRT) to a dose of 30 Gy in ten fractions daily. Pre-radiotherapy (1)H-MR spectroscopy focused on the h-tNAA concentration and memory testing was performed. Memory was evaluated by Auditory Verbal Learning Test (AVLT) and Brief Visuospatial Memory Test-Revised (BVMT-R). Total recall, recognition and delayed recall were reported. The both investigation procedures were repeated 4 months after WBRT and the h-tNAA and memory changes were correlated. RESULTS: Of the 20 patients, ten passed whole protocol. The h-tNAA concentration significantly decreased from pre-WBRT 8.9, 8.86 and 8.88 [mM] in the right, left and both hippocampi to 7.16, 7.65 and 7.4 after WBRT, respectively. In the memory tests a significant decrease was observed in AVLT total-recall, BVMT-R total-recall and BVMT-R delayed-recall. Weak to moderate correlations were observed between left h-tNAA and AVLT recognition and all BVMT-R subtests and between the right h-tNAA and AVLT total-recall. CONCLUSIONS: A significant decrease in h-tNAA after WBRT was proven by (1)H-MR spectroscopy as a feasible method for the in vivo investigation of radiation injury. Continuing patient recruitment focusing on other cognitive tests and metabolites is needed.
Keywords: senioři; Brain Neoplasms; Neuropsychological Tests; Magnetic Resonance Spectroscopy; Memory; magnetická rezonanční spektroskopie; hipokampus; radiační poranění; Kaplan-Meier Estimate; Cognition Disorders; Middle Aged; mužské pohlaví; Radiation Injuries; Kaplanův-Meierův odhad; Aspartic Acid; Cranial Irradiation; kognitivní poruchy; paměť; ženské pohlaví; neuropsychologické testy; kyselina asparagová; Humans; biologické markery; lidé středního věku; nádory mozku; Protons; kraniální ozáření; Biomarkers; Female; Aged; lidé; Male; Hippocampus; protony